Pengaruh Komposisi Media Tanam Berbasis Pupuk Kandang terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascolanicum L.) - Hasmila; Laode Afa; Norma Arif (LP3M Universitas Muhammadiyah Kendari, 2022)
The Shallot requires soil types with a high fertility level in terms of physical, chemical and biological aspects. The research aims to determine the effect of the composition of growing media based on manure on growth and yield shallot. The research design used was a randomized block design with 10 treatments, i.e. P0 = soil media (control), P1 = soil: sands: cow manure (1:1:1), P2 = soil: sands: chicken manure (1:1:1), P3 = soil: sands: goat munere (1:1:1), P4 = soil: sands: cow manure (2:1:2), P5 = soil: sands: chicken manure (2:1:2), P6 = soil: sands: goat munere (2:1:2), P7 = soil: sands: cow manure (3:1:3), P8 = soil: sands: chicken manure (3:1:3), P9 = soil: sands: goat munere (3:1:3). The analysis of data on plant height, leaf number, number of tillers, number of tubers, fresh weight and dry weight tubers per plant, using ANOVA, if analysis result of significant (Fhit> Ftab) then continue with BNJ test on α=0.05. The results showed that the composition of growing media based on manure, soil: sand: cow manure (3:1:3) can improve the yield of shallot a 464,35% compared to the growth media of soils.